2001
DOI: 10.1159/000049005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Rotational Stress of Different Duration on NK Cell Activity, Proinflammatory Cytokines, and POMC-Derived Peptides in Mice

Abstract: Previous studies have shown that the same stressor, depending on intensity, controllability, or duration, can have different effects on the immune system. The purpose of this study was to determine the effect of 10- and 20-min rotation on natural killer (NK) cell activity and also to establish if changes in body temperature, proinflammatory cytokine (IL-1β, IL-6, and TNF-α) levels, and proopiomelanocortin (POMC)-derived peptide (ACTH and β-endorphin) levels parallel the changes in NK cell activity in mice. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 33 publications
(41 reference statements)
0
9
0
Order By: Relevance
“…Furthermore, because CM6271 had no clear effect on the changes caused by restraint in the blood levels of immunosuppressive corticosterone or in the lipid peroxide level in the liver, it is suggested that actions on the immune system through direct action on the endocrine system and the oxidation-reduction system are unlikely. In relation to a possible mode of action, mediated by the immune system, for the effect of CM6271 on NK cell activity, we observed no effect on the blood levels of cytokines IL-6 and TNF-a, whose production is reported to be altered by stress loading (Hale et al, 2001;Nukina et al, 2001).…”
Section: Discussionmentioning
confidence: 68%
“…Furthermore, because CM6271 had no clear effect on the changes caused by restraint in the blood levels of immunosuppressive corticosterone or in the lipid peroxide level in the liver, it is suggested that actions on the immune system through direct action on the endocrine system and the oxidation-reduction system are unlikely. In relation to a possible mode of action, mediated by the immune system, for the effect of CM6271 on NK cell activity, we observed no effect on the blood levels of cytokines IL-6 and TNF-a, whose production is reported to be altered by stress loading (Hale et al, 2001;Nukina et al, 2001).…”
Section: Discussionmentioning
confidence: 68%
“…BE is primarily synthesised in the hypothalamus and the anterior and intermediate lobes of the pituitary (Stratakis and Chrousos 1995;Smith and Funder 1988), but also in monocytes, granulocytes, lymphocytes and macrophages (Mousa et al 2004). Stress significantly increases the BE concentration in plasma and within immune cells (Sacerdote et al 1994;Tsukada et al 2001), which together could contribute to stressinduced immunomodulation (Hale et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Given that TNF-· may also contribute to the neuroendocrine effects elicited by the bacterial endotoxin, lipopolysaccharide (LPS) [16], the role of p55 was also investigated in this respect. Finally, since psychogenic stressors have been reported to increase TNF-· levels [17], coupled with the finding that other cytokines such as IL-1 have been implicated in immobilization-induced HPA activation. [18], it was of interest to determine whether p55 contributes to HPA activation elicited by a restraint or auditory stressor.…”
Section: Introductionmentioning
confidence: 93%